Integrating agriculture, conservation and ecotourism examples from the field - Campbell, W. Bruce; Ortiz, Silvia Lopez (Issues in Agroecology - Present Status and Future Prospectus, 2011)
Issues In Agroecology integrates agriculture, ecology, sociology, anthropology, environmental sciences, ethics, economics, rural development, sustainability, policy and education. The series approaches this complex panorama of topics by presenting authoritative, comprehensive, and analytical reviews from leading scientists in all areas of agroecology worldwide. Authors are invited and represent a collaborative mix to provide strong summaries and scholarly advances that serve as foundations for discussion leading to novel routes of research activity, application of management methodologies, and education and outreach programs. Each review is a concise and up-to-date synthesis of the rapidly growing quantity of scientific information within this highly interdisciplinary field. The authors for each review assess the present status of the knowledge as to whether or not it is effectively contributing to increased sustainability. As a part of this assessment, the authors identify inadequacies, errors, and gaps in knowledge that may be hindering or opposing sustainability objectives. For each review, the authors ultimately discuss what might be needed to bring work and programs onto a better track towards achieving sustainability. Such informed assessments of the routes to realize future potential go beyond the individual farm to include landscapes, communities, and biogeographic regions by emphasizing their unique agricultural and ecological values, and their biological, societal, and cultural components and processes. As a result of these efforts, this series is an essential part of the scientific method and a necessity for researchers, teachers, students, and field professionals when dealing with increasing global environmental and socioeconomic change. Issues In Agroecology is a highly citable series that is guaranteed to enlighten research teams, technology users, educators, students, and the general public on the status and advances of agroecology worldwide.